2004
DOI: 10.1023/b:qure.0000018491.80646.bc
|View full text |Cite
|
Sign up to set email alerts
|

Radiation related morbidities and their impact on quality of life in head and neck cancer patients receiving radical radiotherapy

Abstract: Although 50-70% of head and neck cancer patients in India receive radiotherapy (RT), radiation-related acute and late morbidities and their impact on quality of life (QOL) are infrequently reported. Acute and late radiation morbidities and QOL were assessed in a prospective longitudinal study of 45 patients with head and neck cancers receiving radical RT to a dose of 7000 cGy in conventional fractionation. Grade II acute morbidities experienced by the largest percent of the sample during the course of RT perta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 15 publications
4
51
0
1
Order By: Relevance
“…Study findings related to symptoms are congruent with published literature regarding symptoms and treatment side effects among head and neck cancer patients [1,3,5,[30][31][32][33]. Patients experienced symptoms as early as the first week of radiation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Study findings related to symptoms are congruent with published literature regarding symptoms and treatment side effects among head and neck cancer patients [1,3,5,[30][31][32][33]. Patients experienced symptoms as early as the first week of radiation.…”
Section: Discussionsupporting
confidence: 87%
“…Uncertainty in illness has been previously observed in other cancer populations [30]. This study is the first to document the presence of uncertainty in illness among oropharyngeal and laryngeal cancer patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The relative frequencies of the radiation morbidity in this study are high but largely similar to those reported in other studies (8)(9)(10)(11). In the literature the most commonly reported radiation side effects are mucositis and xerostomia, both estimated at 80% (10, 12), skin reaction estimated at 90% (13), pain and suffering estimated at 69% (11) and pain on swallowing estimated at 56% (14).…”
Section: Discussionsupporting
confidence: 71%
“…Синдром сухого рта выявляет-ся с высокой частотой у пациентов с опухолями головы и шеи, после проведения радиотерапии, химиотерапии и лучевой терапии [24][25][26][27]. Установлено, что уже при подве-дении суммарной очаговой дозы 10 Гр, после первой неде-ли лечения отмечается существенное снижение слюноот-деления на 50-60%, а степень поражения слюнных желез напрямую зависит от общей дозы облучения [28,29].…”
unclassified